ACC meanders, energy transfer, and barotropic–baroclinic instability - Youngs, Madeleine K.; Thompson, Andrew F.; Lazar, Ayah; Richards, Kelvin (Journal of Physical Oceanography, 2017)
Author Posting. © American Meteorological Society, 2017. This article is posted here by permission of American Meteorological Society for personal use, not for redistribution. The definitive version was published in Journal of Physical Oceanography 47 (2017): 1291-1305, doi:10.1175/JPO-D-16-0160.1. Along-stream variations in the dynamics of the Antarctic Circumpolar Current (ACC) impact heat and tracer transport, regulate interbasin exchange, and influence closure of the overturning circulation. Topography is primarily responsible for generating deviations from zonal-mean properties, mainly through standing meanders associated with regions of high eddy kinetic energy. Here, an idealized channel model is used to explore the spatial distribution of energy exchange and its relationship to eddy geometry, as characterized by both eddy momentum and eddy buoyancy fluxes. Variations in energy exchange properties occur not only between standing meander and quasi-zonal jet regions, but throughout the meander itself. Both barotropic and baroclinic stability properties, as well as the magnitude of energy exchange terms, undergo abrupt changes along the path of the ACC. These transitions are captured by diagnosing eddy fluxes of energy and by adopting the eddy geometry framework. The latter, typically applied to barotropic stability properties, is applied here in the depth–along-stream plane to include information about both barotropic and baroclinic stability properties of the flow. These simulations reveal that eddy momentum fluxes, and thus barotropic instability, play a leading role in the energy budget within a standing meander. This result suggests that baroclinic instability alone cannot capture the dynamics of ACC standing meanders, a challenge for models where eddy fluxes are parameterized. The authors all acknowledge support from NSF OCE-1235488. MKY also acknowledges support from the AMS Graduate Student Fellowship. 2017-10-12